Parametric study of the along-wind and across-wind responses of tall RC chimneys using the frequency domain analysis - Houshyar Eimani kalehsar (Iranian Society of Structrual Engineering (ISSE), 2017)
Tall industrial chimneys are sensitive structures to dynamic wind loads. Design codes generally provide approximate equations to estimate the wind-induced response of tall structures. However, they require dynamic analysis to determine the accurate response of slender and sensitive structures. In the present study, dynamic responses of 100-400 m tall RC chimneys under the random wind loads are determined using the frequency domain analysis. Due to the dominant bending mode, the structure of the chimney is modeled as a multi-degree-of-freedom (MDOF) lumped-mass system. All the modeling and analysis procedure, including element meshing, determining the transfer matrix, calculating the along-wind and across-wind force spectrum matrices, and the numerical integration to obtain the responses, are carried out using MATLAB software. The effect of different design parameters, such as chimney height, top diameter to base diameter ratio, basic wind velocity, and terrain category on the wind-induced response of structures, is investigated. The results indicate that the coefficient of variation (CV) of the along-wind response increases with increasing the basic wind velocity. The maximum across-wind responses of the studied chimneys occur in the basic wind velocity range of 10 to 20 m/sec. The across-wind response significantly decreases as the ratio of top diameter to base diameter of the chimney decreases.